2004
DOI: 10.1248/bpb.27.185
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Phytoestrogens with Estrogen Receptors .ALPHA. and .BETA. (III). Estrogenic Activities of Soy Isoflavone Aglycones and Their Metabolites Isolated from Human Urine

Abstract: The intake of weakly estrogenic isoflavonoids (phytoestrogens) is high in countries with a low incidence of estrogenrelated cancers, such as breast and prostate cancers. 1) Two ERs (a and b ) have been identified to date and the physiological responses of estrogens are known to be mediated within specific tissues by at least these two receptors.2,3) The ERs are a 3A member of the nuclear hormone receptor family and act as a ligand-activated nuclear transcription factor. 4)In a previous paper, we reported the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
79
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 15 publications
6
79
0
4
Order By: Relevance
“…In many in vitro studies with MCF-7 cells, soy isoflavones have been shown to increase the proliferation of the cells in concentration dependent manner 6,36,37 and to inhibit apoptosis, 38 which agrees with the findings in MCF-7 xenograft model in vivo showing increased tumor growth via increased cell proliferation after consumption of isoflavone-rich diets. 9,11,22 The mammalian lignan metabolites of plant lignans in FS, enterodiol and especially enterolactone, have also been shown to increase the MCF-7 cell proliferation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In many in vitro studies with MCF-7 cells, soy isoflavones have been shown to increase the proliferation of the cells in concentration dependent manner 6,36,37 and to inhibit apoptosis, 38 which agrees with the findings in MCF-7 xenograft model in vivo showing increased tumor growth via increased cell proliferation after consumption of isoflavone-rich diets. 9,11,22 The mammalian lignan metabolites of plant lignans in FS, enterodiol and especially enterolactone, have also been shown to increase the MCF-7 cell proliferation.…”
Section: Discussionsupporting
confidence: 84%
“…3,4 The biological effects of lignans have been attributed particularly to enterolactone, which has been suggested to act as an endocrine active compound. In vitro, both soy isoflavones and enterolactone have been demonstrated to interact with estrogen receptor (ER) a and b. Soy isoflavones bind and transactivate both ERs with high affinity 5,6 while enterolactone binds weakly to ERs 7 and activate gene expression via ERs at high concentration. 7,8 Isoflavone and lignan-rich diets are reported to have distinct effects on the growth of estrogen responsive tumors in vivo.…”
mentioning
confidence: 99%
“…31 However, isoflavones predominantly circulate in conjugated forms 32 and their bioactivity is thought to be markedly less potent than unconjugated forms in terms of binding to the oestrogen receptor and stimulation of transcription. 33 Results from several intervention studies in humans have also suggested that exposure to dietary isoflavones may alter oestrogen metabolism, [34][35][36][37][38][39] although findings from other similar studies have been inconsistent. [40][41][42] Consistent with the null findings in the current study, the majority of previous prospective studies of dietary isoflavone intake and risk for breast cancer have failed to find a strong association, [10][11][12]43 while results from one study suggested a protective association.…”
Section: Main Findingsmentioning
confidence: 99%
“…The putative beneficial health effects of isoflavones are based on their structural similarity to the mammalian estrogen 17β-estradiol. Due to this analogy, they may compete with estrogens in binding to estrogen receptors and show weak estrogenic activities (Kinjo et al 2004).…”
mentioning
confidence: 99%